Molecular Epidemiology of Herpangina Children in Tongzhou District, Beijing, China, During 2019-2020 - Xie, Ming-Zhu; Chen, Lin-Yi; Yang, Yan-Na; Cui, Yan; Zhang, Si-Hui; Zhao, Tian-Shuo; Zhang, Wan-Xue; Du, Juan; Cui, Fu-Qiang; Lu, Qing-Bin (Frontiers in Medicine, 2022)
Background The changing pattern of pathogen spectrum causing herpangina in the time of coronavirus disease 2019 (COVID-19) pandemic was unknown. The purpose of this study was to investigate the changes on the molecular epidemiology of herpangina children during 2019-2020 in Tongzhou district, Beijing, China. Method From January 2019 to December 2020, children diagnosed with herpangina were recruited by the staff from Tongzhou Center for Disease Control and Prevention (CDC) in Beijing. Viral RNA extraction from pharyngeal swabs was used for enterovirus (EV) detection and the complete VP1 gene was sequenced. The phylogenetic analysis was performed based on all VP1 sequences for EV genotypes. Result A total of 1331 herpangina children were identified during 2019-2020 with 1121 in 2019 and 210 in 2020 respectively. The predominant epidemic peak of herpangina children was in summer and autumn of 2019, but not observed in 2020. Compared to the number of herpangina children reported in 2019, it decreased sharply in 2020. Among 129 samples tested in 2019, 61 (47.3%) children were detected with EV, while 22.5% (20/89) were positive in 2020. The positive rate for EV increased since June 2019, peaked at August 2019, and decreased continuously until February 2020. No cases were observed from February to July in 2020, and the positive rate of EV rebounded to previous level since August 2020. Four genotypes, including CV-A6 (9.3%), CV-A4 (7.8%), CV-A10 (2.3%) and CV-A16 (10.1%), were identified in 2019, and only three genotypes, including CV-A6 (9.0%), CV-A10 (6.7%) and CV-A16 (1.1%), were identified in 2020. The phylogenetic analysis showed that all CV-A6 strains from Tongzhou located in Group C, and the predominant strains mainly located in C2-C4 subgroups during 2016-2018 and changed into C1 subgroup during 2018-2020. CV-A16 strains mainly located in Group B, which consisting of strains widely distributed around the world. Conclusions The predominant genotypes gradually shifted from CV-A16, CV-A4 and CV-A6 in 2019 to CV-A6 in 2020 under COVID-19 pandemic. Genotype-based surveillance will provide robust evidence and facilitate the development of public health measures.